Method for recovering lithium from silicon-based negative electrode material

By roasting and immersion with the acid in the carbon dioxide atmosphere, the lithium is efficiently recovered from the silicon -based negative electrode material, and the environmental pollution and equipment corrosion of the existing technology are solved. Cyclone with resources.

CN119372482APending Publication Date: 2025-01-28ZHEJIANG XINSHIDAI ZHONGNENG RECYCLING TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411517519.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The prior art When recovering lithium from silicon-based anode materials, there are problems such as the use of hydrofluoric acid to cause environmental pollution and equipment corrosion, which limits its long-term application in industry.

Method used

Bake the silicon -based pole material in the carbon dioxide atmosphere, and then mixes with sulfuric acid, hydrochloric acid or nitrate acid liquid, and control the immersion temperature at 30-95 ° C to extract lithium -containing solution.

Benefits of technology

This method does not need to use hydrofluoric acid to reduce the risk of environmental pollution and equipment corrosion, increase the recovery rate of lithium, reduce production costs, suitable for long -term application of industrialization, and promote the recycling of resources.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a method for recovering lithium from a silicon-based negative electrode material, which comprises the following steps: roasting the silicon-based negative electrode material in a carbon dioxide-containing atmosphere, cooling the roasted product, mixing with acid, leaching, controlling the temperature at 30-95 DEG C in the leaching process, carrying out solid-liquid separation, and collecting the liquid phase part to obtain a lithium-containing solution, the acid comprises at least one of sulfuric acid, hydrochloric acid or nitric acid. The core step of the scheme of the invention firstly relates to roasting treatment on the silicon-based negative electrode material under the atmosphere condition containing carbon dioxide. The treatment process ingeniously realizes effective conversion of lithium silicate in the material, and creates favorable conditions for subsequent extraction of lithium element. Next, the converted lithium compound can be dissolved through an acid leaching process, and a system is separated into a lithium-containing solution and solid residues through filtering operation; the lithium-containing solution can be further processed and prepared into various lithium salt products, and residual solid residues also have recycling value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field related to lithium battery material recovery, and in particular to a method for extracting lithium from silicon-based negative electrode materials. Background Art

[0002] Silicon-based negative electrode materials are regarded as the potential star of the next generation of high-energy-density lithium-ion battery negative electrode materials due to their many significant advantages. These advantages include higher theoretical specific capacity, which means that more energy can be stored; lower delithiation potential, which is conducive to improving the working voltage and efficiency of the battery; environmental friendliness, which meets the requirements of sustainable development; abundant natural reserves, which ensure the stability of raw material supply; and relatively low cost, which helps to reduce the overall manufacturing cost of the battery. However, silicon-based negative electrode materials also face two major challenges in practical applications: first, their intrinsic conductivity is low, which affects the electron transmission efficiency inside the battery; second, during the lithium ion deintercalation process, silicon materials will undergo significant volume changes, which can easily lead to the destruction of the electrode structure, and then cause the battery capacity to decay rapidly and the cycle performance to drop sharply. In view of these problems, the research on silicon-based negative electrode materials has attracted a lot of attention and investment from scientific researchers in recent years.

[0003] At present, the research on silicon-based negative electrode materials is in a rapid development stage, and some research results have been successfully applied to the commercial production of lithium-ion batteries, indicating that it is gradually moving towards replacing traditional graphite carbon materials and becoming the mainstream negative electrode material. In view of this, the research on the recycling technology of silicon-based negative electrode materials is particularly important, which not only helps the recycling of resources, but also reduces the pressure on the environment.

[0004] For lithium silicates, a type of silicon-based negative electrode material, due to its high ion conductivity and excellent initial charge and discharge efficiency, the preparation of composite silicon-based negative electrode materials through doping strategies has become an effective way to improve the overall performance of batteries. It is worth noting that although research on the recycling of this type of negative electrode material is still insufficient, the lithium content it contains is not low. Against the background of increasingly tight global lithium resources, the recycling and reuse of lithium silicate negative electrode materials is particularly urgent.

[0005] Patent CN 115557520 A proposes a method for recovering lithium from lithium silicate waste residue, which relies on the dissolution of hydrofluoric acid, followed by the addition of sulfuric acid and heating to volatilize HF, and finally obtains a lithium sulfate solution. However, this method has the risk of environmental pollution and equipment corrosion, which limits its long-term application in industry. In view of this, the development of a lithium recovery technology for silicon-based negative electrode materials that does not require the use of hydrofluoric acid, is environmentally friendly, and is suitable for long-term industrial application is of great significance for promoting the sustainable development of silicon-based negative electrode materials and the green transformation of the lithium-ion battery industry. Summary of the invention

[0006] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention provides a method for recovering lithium from silicon-based negative electrode materials, which does not require the use of HF during the recovery process and is suitable for long-term industrial applications.

[0007] A method for recovering lithium from a silicon-based negative electrode material according to an embodiment of the present invention comprises the following steps:

[0008] The silicon-based negative electrode material is calcined in a carbon dioxide-containing atmosphere, and the calcined product is cooled and mixed with an acid for leaching. During the leaching process, the temperature is controlled at 30 to 95° C., the solid and liquid are separated, and the liquid phase is collected to obtain a lithium-containing solution. The acid includes at least one of sulfuric acid, hydrochloric acid or nitric acid.

[0009] According to the method of the embodiment of the present invention, there are at least the following beneficial effects: the present invention proposes an innovative silicon-based negative electrode material processing scheme, and its core step first involves roasting the silicon-based negative electrode material under an atmosphere containing carbon dioxide. This treatment process cleverly realizes the effective conversion of lithium silicates in the material, creating favorable conditions for the subsequent extraction of lithium elements. Next, through the acid leaching process, the converted lithium compounds can be dissolved, and through the solid-liquid separation operation, the system can be separated into two parts: a lithium-containing solution and a solid slag. The lithium-containing solution can be further processed to prepare various lithium salt products, and the remaining solid slag is also worth recycling.

[0010] Controlling the temperature within a suitable range during the acid leaching process can not only make lithium elements more easily dissolve in the acid solution, but also help reduce the corrosion of equipment and pipelines and reduce maintenance costs. Properly controlling the temperature between 30 and 95°C not only ensures the efficient recovery of lithium elements, but also allows the acid leaching process to operate at a lower energy consumption, avoiding the extra energy consumption caused by excessively high or low temperatures. At the same time, stable temperature control helps maintain the stability of the acid leaching process, making the entire production process more controllable and reliable; ensuring the stability and consistency of product quality and improving production efficiency. Appropriate temperature can prevent thermal deformation of silicon-based negative electrode materials and acid leaching equipment due to overheating, thereby extending the service life of materials and equipment, helping to reduce the corrosion of equipment and pipelines, reducing maintenance costs, and is suitable for long-term industrial applications.

[0011] Compared with the traditional method of extracting lithium using hydrofluoric acid (HF), the process of the present invention shows significant environmental friendliness, ease of operation and high efficiency. It not only greatly improves the recovery rate of lithium, but also effectively reduces the production cost, making the entire process more economical and feasible, and very suitable for large-scale industrial production applications. In addition, during the treatment process, the method maintains good chemical stability for silicon and carbon materials in the solid slag, avoids unnecessary loss or pollution, and opens up a new way for the further recycling of these materials.

[0012] The silicon and carbon components of the solid slag produced by the present invention are not affected, so it can be deeply processed by referring to the existing technology (such as the carbonization treatment step described in patent CN 112320802A) to achieve efficient recycling of resources. This feature not only improves the resource utilization rate of the entire processing flow, but also promotes the development of a green circular economy, and has far-reaching significance for promoting the sustainable development of silicon-based negative electrode materials and even the entire battery industry.

[0013] According to some embodiments of the present invention, the silicon-based negative electrode material contains lithium silicate.

[0014] According to some embodiments of the present invention, the lithium silicate includes at least one of Li2SiO3, Li2Si2O5, Li4SiO4, and Li6Si2O7.

[0015] According to some embodiments of the present invention, the carbon dioxide-containing atmosphere is air or a mixture of carbon dioxide and other gases.

[0016] According to some embodiments of the present invention, the other gas may be at least one of nitrogen, argon, and the like.

[0017] According to some embodiments of the present invention, the volume concentration of carbon dioxide in the carbon dioxide-containing atmosphere is 0.03-3%.

[0018] According to some embodiments of the present invention, the calcination temperature is 200-700°C.

[0019] According to some embodiments of the present invention, the calcination temperature is 400-630°C.

[0020] According to some embodiments of the present invention, the calcination time is 1 to 20 hours.

[0021] According to some embodiments of the present invention, the leaching process includes at least one of the following conditions:

[0022] 1) Liquid-to-solid ratio is 2-30;

[0023] 2) Acid concentration is 1-10 mol / L;

[0024] 3) The reaction time is 1-5h.

[0025] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. DETAILED DESCRIPTION

[0026] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of them. Based on the embodiments of the present invention, other embodiments obtained by technicians in this field without creative work are all within the scope of protection of the present invention. The test methods used in the embodiments are conventional methods unless otherwise specified; the materials, reagents, etc. used, unless otherwise specified, can be reagents and materials obtained from commercial channels. Unless otherwise specified, the same parameter in each embodiment has the same value. The embodiments described below are exemplary and are only used to explain the present invention, and cannot be understood as limitations on the present invention.

[0027] In the description of the present invention, the description with reference to the term "some embodiments" or the like means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0028] The "room temperature" referred to in the present invention refers to 25±5°C.

[0029] The liquid-to-solid ratio referred to in the present invention is the mass ratio of liquid to solid.

[0030] In some embodiments of the present invention, a method for recovering lithium from a silicon-based negative electrode material comprises the following steps:

[0031] The silicon-based negative electrode material is calcined in a carbon dioxide-containing atmosphere, and the calcined product is cooled and mixed with an acid for leaching. During the leaching process, the temperature is controlled at 30 to 95° C., the solid and liquid are separated, and the liquid phase is collected to obtain a lithium-containing solution. The acid includes at least one of sulfuric acid, hydrochloric acid or nitric acid.

[0032] The present invention proposes an innovative silicon-based negative electrode material processing scheme, the core step of which first involves calcining the silicon-based negative electrode material under an atmosphere containing carbon dioxide. This treatment process cleverly achieves the effective conversion of lithium silicates in the material, creating favorable conditions for the subsequent extraction of lithium elements. Next, the converted lithium compounds can be dissolved through an acid leaching process, and the system can be separated into two parts, a lithium-containing solution and a solid slag, through a filtration operation. The lithium-containing solution can be further processed into various lithium salt products, and the remaining solid slag is also worth recycling.

[0033] Controlling the temperature within a suitable range during the acid leaching process can not only make lithium elements more easily dissolve in the acid solution, but also help reduce the corrosion of equipment and pipelines and reduce maintenance costs. Properly controlling the temperature between 30 and 95°C not only ensures the efficient recovery of lithium elements, but also allows the acid leaching process to operate at a lower energy consumption, avoiding the extra energy consumption caused by excessively high or low temperatures. At the same time, stable temperature control helps maintain the stability of the acid leaching process, making the entire production process more controllable and reliable; ensuring the stability and consistency of product quality and improving production efficiency. Appropriate temperature can prevent thermal deformation of silicon-based negative electrode materials and acid leaching equipment due to overheating, thereby extending the service life of materials and equipment, helping to reduce the corrosion of equipment and pipelines, reducing maintenance costs, and is suitable for long-term industrial applications.

[0034] Compared with the traditional method of extracting lithium using hydrofluoric acid (HF), the process of the present invention shows significant environmental friendliness, ease of operation and high efficiency. It not only greatly improves the recovery rate of lithium, but also effectively reduces the production cost, making the entire process more economical and feasible, and very suitable for large-scale industrial production applications. In addition, during the treatment process, the method maintains good chemical stability for silicon and carbon materials in the solid slag, avoids unnecessary loss or pollution, and opens up a new way for the further recycling of these materials.

[0035] The silicon and carbon components of the solid slag produced by the present invention are not affected, so it can be deeply processed by referring to the existing technology (such as the carbonization treatment step described in patent CN 112320802A) to achieve efficient recycling of resources. This feature not only improves the resource utilization rate of the entire processing flow, but also promotes the development of a green circular economy, and has far-reaching significance for promoting the sustainable development of silicon-based negative electrode materials and even the entire battery industry.

[0036] According to some embodiments of the present invention, the silicon-based negative electrode material contains lithium silicate.

[0037] Lithium silicate, as an important component of silicon-based negative electrode materials, not only has excellent ion conductivity, but the scheme of the present invention also cleverly releases lithium elements through chemical reactions, which is convenient for subsequent extraction and recovery. The scheme of the present invention fundamentally improves the recyclability and resource utilization of silicon-based negative electrode materials.

[0038] According to some embodiments of the present invention, the lithium silicate includes at least one of Li2SiO3, Li2Si2O5, Li4SiO4, and Li6Si2O7.

[0039] The solution of the present invention can be applied to various application scenarios and requirements.

[0040] According to some embodiments of the present invention, the carbon dioxide-containing atmosphere is air or a mixture of carbon dioxide and other gases.

[0041] According to some embodiments of the present invention, the other gas may be at least one of nitrogen, argon, and the like.

[0042] The use of a mixed atmosphere of carbon dioxide and other gases (such as air, nitrogen, and argon) not only ensures the stability of the gas atmosphere during the roasting process, but also avoids the potential safety hazards caused by a single gas. The introduction of carbon dioxide promotes the conversion of lithium silicates and reduces environmental risks.

[0043] According to some embodiments of the present invention, the volume concentration of carbon dioxide in the carbon dioxide-containing atmosphere is 0.03-3%.

[0044] Since lithium silicates prepared by different methods are different, those skilled in the art can adjust the carbon dioxide concentration according to actual conditions, such as 0.04%, 0.05%, 1%, 1.5%, 2%, 2.5% or 3%.

[0045] The volume concentration range of 0.03-3% enables the process of the present invention to operate under a wide range of conditions and adapt to lithium silicates with different preparation methods and raw material characteristics. This flexibility helps to optimize process conditions and improve lithium recovery efficiency and overall material performance.

[0046] According to some embodiments of the present invention, the calcination temperature is 200-700°C.

[0047] According to some embodiments of the present invention, the calcination temperature is 400-630°C.

[0048] Lithium silicate materials can also adsorb carbon dioxide at room temperature, but the adsorption rate is slow and it takes a long time to reach the maximum adsorption amount; in addition, the adsorption temperature of lithium silicate prepared by different methods will also vary.

[0049] The calcination temperature range of 200-700°C (such as 400-630°C, specifically 450°C, 500°C, 550°C, 600°C, etc.) ensures the effective conversion of lithium silicate and avoids excessive sintering or decomposition of materials at high temperatures. The selection within this temperature range makes the process more controllable and improves the quality and stability of the product.

[0050] According to some embodiments of the present invention, the calcination time is 1 to 20 hours.

[0051] The holding time can be adjusted according to actual conditions, such as 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, etc. The calcination time of 1 to 20h provides sufficient reaction time for the process and ensures the full conversion of lithium silicate. At the same time, this time range also adapts to the needs of different production scales and efficiencies, and improves the flexibility and applicability of the process.

[0052] According to some embodiments of the present invention, the leaching process includes at least one of the following conditions:

[0053] 1) Liquid-to-solid ratio is 2-30;

[0054] 2) Acid concentration is 1-10 mol / L;

[0055] 3) The reaction time is 1-5h.

[0056] The optimization of liquid-to-solid ratio, acid concentration and reaction time makes the leaching process more efficient and controllable. Adjustment of these parameters helps to improve the leaching rate and purity of lithium, while reducing energy consumption and costs. The selection of liquid-to-solid ratio and acid concentration ensures the full progress of the acid leaching process, while the control of reaction time avoids unnecessary energy consumption and pollution.

[0057] The “recovered silicon-based negative electrode powder” used in the following examples and comparative examples is from the same source.

[0058] Example 1

[0059] This example provides a method for extracting lithium from a silicon-based negative electrode material, and the specific steps are as follows:

[0060] (1) Weigh 100 g of the recovered silicon-based negative electrode powder into a crucible, put it into a tube furnace and introduce air, the carbon dioxide concentration in the air is about 0.04% vol, and then roast it at a temperature of 500° C. for 12 h. After the roasting is completed, the material is cooled and taken out;

[0061] (2) Weigh 50 g of the calcined product, add 2 mol / L sulfuric acid solution, with a liquid-to-solid ratio of 30, and a temperature of 85° C., stir to react for 2 h, and filter and separate to obtain a lithium-containing solution.

[0062] The results show that the lithium ion leaching rate reaches 98.81% during the acid leaching process of lithium.

[0063] Example 2

[0064] This example provides a method for extracting lithium from a silicon-based negative electrode material, and the specific steps are as follows:

[0065] (1) Weigh 200 g of silicon-based negative electrode powder into a crucible, put it into a tube furnace and introduce a mixture of carbon dioxide and nitrogen, with a carbon dioxide concentration of about 0.5% vol, and then calcine it at a temperature of 500° C. for 6 hours. After the calcination is completed, wait for the material to cool down and then take it out;

[0066] (2) Weigh 50 g of the calcined product, add 2 mol / L sulfuric acid solution, with a liquid-to-solid ratio of 6, and a temperature of 85° C., stir to react for 2 h, and filter and separate to obtain a lithium-containing solution.

[0067] The results show that the lithium ion leaching rate reaches 99.78% during the acid leaching process of lithium.

[0068] Example 3

[0069] This example provides a method for extracting lithium from a silicon-based negative electrode material, and the specific steps are as follows:

[0070] (1) Weigh 100 g of silicon-based negative electrode powder into a crucible, put it into a tube furnace and introduce a mixture of carbon dioxide and nitrogen, with a carbon dioxide concentration of about 3% vol, and then calcine it at a temperature of 400° C. for 0.5 h. After the calcination is completed, wait for the material to cool down and then take it out;

[0071] (2) Weigh 50 g of the calcined product, add 2 mol / L sulfuric acid solution, with a liquid-to-solid ratio of 3.5, and a temperature of 50° C., stir to react for 2 h, and filter and separate to obtain a lithium-containing solution.

[0072] The results show that the lithium ion leaching rate reaches 86.92% during the acid leaching process of lithium.

[0073] Example 4

[0074] This example provides a method for extracting lithium from a silicon-based negative electrode material, and the specific steps are as follows:

[0075] (1) Weigh 200 g of silicon-based negative electrode powder into a crucible, put it into a tube furnace and introduce a mixture of carbon dioxide and nitrogen, with a carbon dioxide concentration of about 3% vol, and then calcine it at 700° C. for 1 h. After the calcination is completed, wait for the material to cool down and then take it out;

[0076] (2) Weigh 50 g of the calcined product, add 2 mol / L sulfuric acid solution, with a liquid-to-solid ratio of 3.5, and a temperature of 50° C., stir to react for 2 h, and filter and separate to obtain a lithium-containing solution.

[0077] The results show that the lithium ion leaching rate reaches 92.32% during the acid leaching process of lithium.

[0078] Example 5

[0079] This example provides a method for extracting lithium from a silicon-based negative electrode material, and the specific steps are as follows:

[0080] (1) Weigh 100 g of silicon-based negative electrode powder into a crucible, put it into a tube furnace, and introduce a mixture of carbon dioxide and nitrogen. The carbon dioxide concentration is about 3% vol. Then, it is roasted at a temperature of 200° C. for 1 h. After the roasting is completed, the material is cooled and taken out;

[0081] (2) Weigh 50 g of the calcined product, add 2 mol / L sulfuric acid solution, with a liquid-to-solid ratio of 3.5, and a temperature of 85° C., stir to react for 2 h, and filter and separate to obtain a lithium-containing solution.

[0082] The results show that the lithium ion leaching rate reaches 56.51% during the acid leaching process of lithium.

[0083] By comparing Example 5 with Example 4, it can be concluded that increasing the roasting temperature is beneficial to further improving the lithium leaching rate.

[0084] Comparative Example 1

[0085] This example provides a method for extracting lithium from a silicon-based negative electrode material, which differs from Example 2 in that no calcination treatment is performed. The specific steps are as follows:

[0086] Weigh 50 g of the raw material, add 2 mol / L sulfuric acid solution, with a liquid-to-solid ratio of 6, the temperature is 85° C., stir to react for 2 h, and filter and separate to obtain a lithium-containing solution.

[0087] The results show that the lithium ion leaching rate is only 33.03% during the acid leaching process of lithium.

[0088] It is concluded from the examples and comparative examples that the lithium leaching rate can be greatly improved after roasting.

[0089] The parameter selection in the present invention not only improves the conversion efficiency of lithium silicate and the recovery rate of lithium, but also optimizes the process conditions, reduces production costs and environmental risks, and provides new ideas and solutions for the recycling of silicon-based negative electrode materials.

[0090] The embodiments of the present invention are described in detail above, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge scope of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.

Claims

1. A method for recovering lithium from a silicon-based negative electrode material, characterized in that: The steps include: The silicon-based negative electrode material is calcined in a carbon dioxide-containing atmosphere, and the calcined product is cooled and mixed with an acid for leaching. During the leaching process, the temperature is controlled at 30 to 95° C., the solid and liquid are separated, and the liquid phase is collected to obtain a lithium-containing solution. The acid includes at least one of sulfuric acid, hydrochloric acid or nitric acid.

2. The method for recovering lithium from a silicon-based negative electrode material according to claim 1, characterized in that: The silicon-based negative electrode material contains lithium silicate.

3. The method for recovering lithium from a silicon-based negative electrode material according to claim 2, characterized in that: The lithium silicate includes at least one of Li2SiO3, Li2Si2O5, Li4SiO4, and Li6Si2O7.

4. The method for recovering lithium from a silicon-based negative electrode material according to any one of claims 1 to 3, characterized in that: The carbon dioxide-containing atmosphere is air or a mixture of carbon dioxide and other gases.

5. The method for recovering lithium from a silicon-based negative electrode material according to claim 4, characterized in that: The other gas is at least one of nitrogen and argon.

6. The method for recovering lithium from a silicon-based negative electrode material according to claim 5, characterized in that: The volume concentration of carbon dioxide in the carbon dioxide-containing atmosphere is 0.03-3%.

7. The method for recovering lithium from a silicon-based negative electrode material according to any one of claims 1 to 3, characterized in that: The calcination temperature is 200-700°C.

8. The method for recovering lithium from a silicon-based negative electrode material according to claim 7, characterized in that: The calcination temperature is 400-630°C.

9. The method for recovering lithium from a silicon-based negative electrode material according to claim 1, characterized in that: The calcination time is 1 to 20 hours.

10. The method for recovering lithium from a silicon-based negative electrode material according to claim 1, characterized in that: The leaching process includes at least one of the following conditions: 1) Liquid-to-solid ratio is 2-30; 2) Acid concentration is 1-10 mol / L; 3) The reaction time is 1-5h.

Citation Information

Patent Citations

  • Recycling method of silicon-carbon negative electrode material

    CN112320802A